ANALISIS DETERMINAN TINGKAT UNDERPRICING SAHAM (STUDI PERUSAHAAN YANG INITIAL PUBLIC OFFERING KETIKA MASA PANDEMI) - Susilowati, Pusvita Indria Mei; Mutahar, Muhammad (Department of Accounting, Faculty of Economics & Business, 2024)
The purpose of this study is to examine the impact of Underwriter's Reputation, Auditor's Reputation, Profitability, Financial Leverage, and Earnings per Share on the amount of stock underpricing. Underwriter's Reputation, Auditor's Reputation, Profitability, Financial Leverage, and Earnings per Share are the independent variables considered in this study. While the degree of stock underprice is the dependent variable used in this study. Companies that made initial public offerings on the Indonesian Stock Exchange during the pandemic make up the study's sample. Purposive sampling was utilized to determine the research sample, and 93 companies were included in the sample. Multiple regression analysis was the method of analysis used in this investigation. The outcomes demonstrated that the Profitability variable, as determined by Return on Assets and Earnings Per Share, had an impact on the degree of stock underprice. The reputations of the underwriter, auditor, and financial leverage have no discernible impact on the degree of underpricing at which the business is currently trading.